PENGARUH PEMBERIAN REBUSAN DAUN SIRIH HIJAU TERHADAP PENYEMBUHAN LUKA PERINIUM PADA IBU POST PARTUM DI KLINIK PERA SIMALINGKAR B KECAMATAN MEDAN TUNTUNGAN KOTA MEDAN TAHUN 2019 - Stefani Anastasia Sitepu; Vitrilina Hutabarat; Kristin Natalia (JURNAL KEBIDANAN KESTRA (JKK), 2020)
Abstrak Postpartum mothers who suffer from perineal injury if not properly maintained and improper care of the perineum can result in infection of the perineum. Care for perineal wounds is carried out by the Indonesian community, one of which is by using green betel leaf decoction water that has an antibiotic effect, based on the effect of this therapy, betel can also be used as material for wound care that is usually used by means of worms. Research to find out whether betel leaf water can accelerate the healing process of perineal wounds in post partum mothers. The research method is pre-experimental using a pretest and posttest design in one group. The sample in this study 31 respondents using non-likely sampling techniques using consecutive sampling method. The results of the study the effect of giving green betel leaf decoction to the healing of perineal wounds in post partum mothers pre-test post-test p-value 0.018 <Î± = 0.05 Ho is rejected, Ha Accepted which means there is an influence of perineal wound healing with green betel leaf decoction in pera simalingkar B clinic, Medan tuntung sub-district, Medan in 2019.